Pengenalan Deteksi Wajah Artificial Intelligence dan Achievement Motivation Training untuk Siswa SMK Kuncup Samigaluh - Sukmasetya, Pristi; Primadewi, Ardhin; Yudianto, Muhammad Resa Arif; Maimunah, Maimunah; Hasani, Rofi Abul; Nugroho, Setiya (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2024)
— Artificial Intelligence (AI) is a field of computer science aimed at developing machines capable of performing tasks that typically require human intelligence. In recent years, the development of AI has shown significant progress, and its use has expanded across various sectors, including education. The application of AI in education offers various opportunities and challenges, such as personalized learning and enhancing students' skills, but also presents challenges in technological adaptation and ethical understanding. This paper discusses the utilization of AI-based facial recognition technology at SMK Kuncup Samigaluh, with the goal of enhancing students' competence in information technology. This community service activity involves a series of structured stages, including initial planning, activity implementation, discussion and Q&A, as well as evaluation and feedback. The results of this activity indicate a significant improvement in students' understanding of AI and facial recognition technology, as evidenced by the increase in post-test scores compared to pre-test scores. With an interactive demonstrative approach, this activity successfully provided a positive impact on students' knowledge and interest in AI, and broadened their horizons regarding career opportunities in information technology.